A study on the mechanism of Beclin-1 m6A modification mediated by catalpol in protection against neuronal injury and autophagy following cerebral ischemia - Kan Liu; Xinyan Yao; Jun Gao; Jinxi Wang; Jing Qi (BMC, 2024)
Abstract Objective Catalpol (CAT) has various pharmacological activities and plays a protective role in cerebral ischemia. It has been reported that CAT played a protective role in cerebral ischemia by upregulaing NRF1 expression. Bioinformatics analysis reveals that NRF1 can be used as a transcription factor to bind to the histone acetyltransferase KAT2A. However, the role of KAT2A in cerebral ischemia remains to be studied. Therefore, we aimed to investigate the role of CAT in cerebral ischemia and its related mechanism. Methods In vitro, a cell model of oxygen and glucose deprivation/reperfusion (OGD/R) was constructed, followed by evaluation of neuronal injury and the expression of METTL3, Beclin-1, NRF1, and KAT2A. In vivo, a MCAO rat model was prepared by means of focal cerebral ischemia, followed by assessment of neurological deficit and brain injury in MCAO rats. Neuronal autophagy was evaluated by observation of autophagosomes in neurons or brain tissues by TEM and detection of the expression of LC3 and p62. Results In vivo, CAT reduced the neurological function deficit and infarct volume, inhibited neuronal apoptosis in the cerebral cortex, and significantly improved neuronal injury and excessive autophagy in MCAO rats. In vitro, CAT restored OGD/R-inhibited cell viability, inhibited cell apoptosis, LDH release, and neuronal autophagy. Mechanistically, CAT upregulated NRF1, NRF1 activated METTL3 via KAT2A transcription, and METTL3 inhibited Beclin-1 via m6A modification. Conclusion CAT activated the NRF1/KAT2A/METTL3 axis and downregulated Beclin-1 expression, thus relieving neuronal injury and excessive autophagy after cerebral ischemia.